Discursive Words in the Karelian Language: Towards the Formulation of the Question - Natalya V. Patroeva; Tatyana V. Pashkova (Финно-угорский мир, 2024)
Introduction. Currently, discursive words in the Karelian language have not been subjected to a comprehensive study, and many questions on the categories of connectors of both closely related and unrelated languages of the world cause controversy and discussion. The solution of these controversial issues is supposed to be possible through the accumulation of a significant amount of linguistic material, as well as data on the pragmatics, evolution, semantics and etymology of discursive words. The purpose of the study is to conduct a comprehensive analysis of the official parts of speech (their composition, functions and semantics) in three dialects of the Karelian language (Karelian proper, Livvikov, Ludikov ones) within the framework of the project “Discursive words in the Karelian language: a comparative typological aspect”.